2008
DOI: 10.1111/j.1472-765x.2008.02414.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration and partial characterization of ecto-ATPase inBalamuthia mandrillarisand its possible role in the host-cell interactions

Abstract: Aims:  To investigate the presence and partial characterization of ecto‐ATPase in Balamuthia mandrillaris. Methods and Results:  In vitro assays were used to demonstrate that live B. mandrillaris hydrolyses extracellular ATP. Using nondenaturing polyacrylamide gel electrophoresis, B. mandrillaris exhibited a single ecto‐ATPase band of molecular mass of more than 545 kDa. This ecto‐ATPase was insensitive to ouabain, levamisole, sodium azide and sodium orthovanadate but stimulated by MgCl2. The ecto‐ATPase was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…As discussed earlier, ADP released from Acanthamoeba castellanii plays an important role in its contact‐independent cytotoxicity, as demonstrated by increased levels of intracellular calcium, which subsequently leads to host cell apoptosis. Similarly, recent findings showed that suramin (P2 receptor antagonist) partially blocked B. mandrillaris binding to and cytotoxicity of human BMEC (Matin & Khan, 2008), demonstrating their role as potential virulence factors in B. mandrillaris ‐mediated dysfunction of the blood–brain barrier.…”
Section: Balamuthia Amoebic Encephalitismentioning
confidence: 69%
See 1 more Smart Citation
“…As discussed earlier, ADP released from Acanthamoeba castellanii plays an important role in its contact‐independent cytotoxicity, as demonstrated by increased levels of intracellular calcium, which subsequently leads to host cell apoptosis. Similarly, recent findings showed that suramin (P2 receptor antagonist) partially blocked B. mandrillaris binding to and cytotoxicity of human BMEC (Matin & Khan, 2008), demonstrating their role as potential virulence factors in B. mandrillaris ‐mediated dysfunction of the blood–brain barrier.…”
Section: Balamuthia Amoebic Encephalitismentioning
confidence: 69%
“…The surface membranes of B. mandrillaris possess ecto‐ATPases (Matin & Khan, 2008). The external localization of the ATP‐hydrolysing site is supported by their sensitivity to suramin, which is a noncompetitive inhibitor of ecto‐ATPases and an antagonist of P2 purinoreceptors, which mediate the physiological functions of extracellular ATP.…”
Section: Balamuthia Amoebic Encephalitismentioning
confidence: 99%
“…mandrillaris is naturally found in soil [273] and occasionally invades humans to cause an insidious infection that can occur in either immunocompetent or immunosuppressed patients. To date, there have been approximately 120 reported cases of Balamuthia encephalitis worldwide, with only two survivors [274]. The incubation period is long and usually results in drastic neurological damage that includes single and multiple space-occupying brain lesions.…”
Section: Pathogenic Free-living Amoeba Speciesmentioning
confidence: 99%
“…In fact, several lines of evidence have suggested the involvement of these enzymes in parasite virulence and infection, indicating that NTPDases might represent a new promising target for rational drug design for antiparasitic chemotherapy (Cohn and Gottlieb, 1997;de Almeida Marques-da-Silva et al, 2008;de Sa Pinheiro et al, 2008;Matin and Khan, 2008;Santos et al, 2009;Sissons et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…A series of evidences have suggested that these enzymes may be involved in eukaryotic events such as: virulence (Berredo-Pinho et al, 2001), purinergic signaling (Deaglio and Robson, 2011;Knowles, 2011), inflammation (Kannan, 2002), hemostasis (Bernardes et al, 2000;Jin et al, 2005;Marcus et al, 2005), purine salvage (de Souza Leite et al, 2007;Lorenz et al, 2007) and host-pathogen interactions (Bisaggio et al, 2003;Matin and Khan, 2008).…”
Section: Introductionmentioning
confidence: 99%